Factors Associated with Lymph Node Metastasis in Special Types of Invasive Breast Cancer at National Cancer Hospital in the Period of 2018 - 2021 - Thi Quynh, Nguyen; Quang Dien, Trinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4DO - 10.25073/2588-1132/vnumps.4332, 2021)
This paper assesses the rate of lymph node metastasis and the correlation between lymph node metastasis and some pathological characteristics in special types of invasive breast cancer. In the paper, a descriptive cross‐sectional study was conducted on 200 patients with special types of invasive breast cancer at the Institute of Molecular Biology and Pathology - National Cancer Hospital from August 2020 to April 2021. The study results show that 32% of the 200 cases had nodal metastases. The factors associated with the increased risk of lymph node metastasis were of histological types (invasive lobular, invasive micropapillary carcinomas) (p = 0.000), high tumour grade (p = 0.000), the presence of lymphovascular invasion (p = 0.000), tumor-infiltrating lymphocytes (TILs) < 10% (p = 0.000), the presence of tumor necrosis (p = 0.001), Her-2/neu overexpression (p = 0.01), Ki-67 ≥ 20% (p = 0.036), HER2-positive breast cancer (p = 0.015).  Overall, the rate of lymph node metastasis was 32%. Histological type, tumour grade, the presence of lymphovascular invasion, TILs, tumor necrosis, Her-2/neu and Ki-67 expression, and molecular subtype were factors related to lymph node metastasis in special types of invasive breast cancer. Keywords: Lymph node metastasis, invasive breast cancer, special types. References [1] World Health Organization, Breast Tumors (5th ed), International Agency for Research on Cancer, Lyon, France, 2019. [2] K. M. Masters, S. L.Wong, R. C. Martin et al., Dermal Injection of Radioactive Colloid Is Superior to Peritumoral Injection for Breast Cancer Sentinel Lymph Node Biopsy: Results of A Multiinstitutional Study, Annals of Surgery, Vol. 233, No. 5, 2001, pp. 676, https://doi.org/10.1097/00000658-200105000-00012. [3] A. V. Ashturkar, G. S. Pathak, S. D. Deshmukh, H. T. Pandave, Factors Predicting the Axillary Lymph Node Metastasis in Breast Cancer: Is Axillary Node Clearance Indicated in Every Breast Cancer Patient? Indian Journal of Surgery, Vol. 73, No. 5,2011, pp. 331-335, https://doi.org/10.1007/s12262-011-0315-5. [4] M. R. Peter, D. L.Michelino, V. Tricia et al., Prediction of Axillary Lymph Node Status in Breast Cancer Patients by Use of Prognostic Indicators, JNCI: Journal of the National Cancer Institute, Vol. 86, No. 23, 1994, pp. 1771-1775, https://doi.org/10.1093/jnci/87.8.607. [5] R. Salgado, C. Denkert, S. Demaria et al., The Evaluation of Tumor-Infiltrating Lymphocytes (TILs) in Breast Cancer: Recommendations by An International TILs Working Group 2014, Annals of Oncology, Vol. 26, No. 2, 2015, pp. 259-271, https://doi.org/10.1093/annonc/mdu450. [6] K. H. Young, Statistical Notes for Clinical Researchers: Chi-Squared Test and Fisher's Exact Test, Restorative Dentistry & Endodontics, Vol. 42, No. 2, 2017, pp. 152-155, https://doi.org/10.5395/rde.2017.42.2.152. [7] L. G. L. Tan, Y. Y. Tan, D. Heng, M. Y. Chan, Predictors of Axillary Lymph Node Metastases in Women with Early Breast Cancer in Singapore, Singapore Med J, Vol. 46, No. 12, 2005, pp. 693, https://doi.org/10.1016/s0959-8049(98)80134-2. [8] A. Barth, P. H. Craig, M. J. Silverstein, Predictors of Axillary Lymph Node Metastases in Patients with T1 Breast Carcinoma, Cancer, Vol. 79, No. 10, 1997, pp. 1918-1922, https://doi.org/10.1002/(SICI)10970142(19970515) 79:10<1918::AID-CNCR12>3.0.CO;2-Y. [9] Y. Iwasaki, Axillary Node Metastasis from T1N0M0 Breast Cancer: Possible Avoidance of Dissection in A Subgroup, Japanese Journal of Clinical Oncology, Vol. 28, No. 10, 1998, pp. 601-603, https://doi.org/10.1093/jjco/28.10.601. [10] G. Viale, S. Zurrida et al., Predicting the Status of Axillary Sentinel Lymph Nodes in 4351 Patients with Invasive Breast Carcinoma Treated in A Single Institution, Cancer, Vol. 103, No. 3, 2005, pp. 492-500, https://doi.org/10.1002/cncr.20809. [11] S. K. Çetintaş, M. Kurt et al., Factors Influencing Axillary Node Metastasis in Breast Cancer, Tumori Journal, Vol. 92, No. 5, 2006, pp. 416-422, https://doi.org/10.1177/030089160609200509. [12] T. V. To, A Study of Morphology, Immunohistochemistry and Their Prognostic Value in Breast Carcinoma, Ph.D Dissertation, Hanoi Medical University, Hanoi, 2004 (in Vietnamese). [13] R. Lauria, F. Perrone et al., The Prognostic Value of Lymphatic and Blood Vessel Invasion in Operable Breast Cancer, Cancer, Vol 76, No. 10, 1995, pp. 1772-1778, https://doi.org/10.1002/1097-0142(19951115)76 :10<1772::AID-CNCR2820761014>3.0.CO;2-O. [14] R. Yerushalmi, M. M. Hayes, K. A. Gelmon, Breast Carcinoma - Rare Types: Review of the Literature, Annals of Oncology, Vol. 20, No. 11, 2009, pp. 1763-1770, https://doi.org/10.1093/annonc/mdp245. [15] A. Caziuc, D. Schlanger, G. Amarinei, Can Tumor-Infiltrating Lymphocytes (TILs) Be a Predictive Factor for Lymph Nodes Status in Both Early Stage and Locally Advanced Breast Cancer?, Vol. 8, No. 5, 2019, pp. 545, https://doi.org/10.3390/jcm8040545. [16] K. Takada, S. Kashiwagi, Y. Asano, Prediction of Lymph Node Metastasis by Tumor-Infiltrating Lymphocytes in T1 Breast Cancer, BMC Cancer, Vol. 20, No. 1, 2020, pp. 598, https://doi.org/10.1186/s12885-020-07101-y. [17] N. T. Ha, Evaluation of Axillary Lymph Node Status and Vascular Infiltration by Molecular Type of Breast Carcinoma, Master Thesis, Hanoi Medical University, Hanoi, 2018 (in Vietnamese). [18] J. Makki, Diversity of Breast Carcinoma: Histological Subtypes and Clinical Relevance, Clinical Medicine Insights: Pathology, Vol. 8, 2015, pp. 23-31, https://doi.org/10.4137/cpath.s31563. [19] L. A. Carey et al, Breast Cancer Subtypes, and Survival in the Carolina Breast Cancer Study, JAMA, Vol. 295, No. 21, 2006, pp. 2492, https://doi.org/10.1001/jama.295.21.2492.